2009
DOI: 10.1080/13693780802369332
|View full text |Cite
|
Sign up to set email alerts
|

Candida bloodstream infections in hemodialysis recipients

Abstract: Candidemia is a major cause of morbidity and mortality in patients undergoing hemodialysis but it has not been well defined in this patient population. We performed a retrospective case-control study to characterize the epidemiology, microbiology, and outcomes of hemodialysis-associated candidemia. All cases of candidemia at our institution were evaluated from 1 January 2000 until 1 September 2004. For each case, two non-candidemic dialysis patients served as controls. Among 350 cases of candidemia, 78 (22%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…Because this finding was apparent in the absence of uremic serum, they concluded that the majority of the functional defect is cell-intrinsic (i.e., the Tregs are defective) rather than cell-extrinsic (uremic toxins, oxidized low-density lipoprotein and hypercytokinemia) [21] . On the other hand, Candida bloodstream infections is one cause of morbidity and mortality in hemodialysis patients [29] and mouse studies have demonstrated that Tregs are required for effective clearance of Candida albicans infections [30] . Thus, effective Treg numbers and functional capacity are important for limiting excess inflammation and properly eradicating some types of infections.…”
Section: Discussionmentioning
confidence: 99%
“…Because this finding was apparent in the absence of uremic serum, they concluded that the majority of the functional defect is cell-intrinsic (i.e., the Tregs are defective) rather than cell-extrinsic (uremic toxins, oxidized low-density lipoprotein and hypercytokinemia) [21] . On the other hand, Candida bloodstream infections is one cause of morbidity and mortality in hemodialysis patients [29] and mouse studies have demonstrated that Tregs are required for effective clearance of Candida albicans infections [30] . Thus, effective Treg numbers and functional capacity are important for limiting excess inflammation and properly eradicating some types of infections.…”
Section: Discussionmentioning
confidence: 99%
“…A little less striking, haemodialysis may be another of these semi‐specific factors predisposing for IC: in a recent retrospective analysis of 350 cases of candidaemia, 22% were adult haemodialysis patients. Candidaemia was associated with a crude hospital mortality rate as high as 52% in haemodialysis patients 12 …”
Section: Patients At Riskmentioning
confidence: 99%
“…Candida albicans infections represent a serious clinical complication in patients with chronic kidney disease (CKD) undergoing haemodialysis treatment and are associated with a high mortality rate [1,2]. The greater risk of infection in this population is caused by impaired host immunity through uraemia, which interferes with T-cell and B-cell function, macrophage phagocytosis and antigen presentation [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%